CIENTIFIC, EDUCATIONAL AND LUDIC POTENCIALITIES OF THE GEOLOGICAL RECORDS PRESENT IN THE ANHANGUERA MUNICIPAL PARK, SÃO PAULO, BRAZIL - Santos-Pletsch, Mikhaela Aloísia Jéssie (2014)
With a total of 950 hectares, the Anhanguera Municipal Park is distant 30 km to the NW from the São Paulo city centre and represents the largest protected green area of public use of the city. Based on the interpretation of remote sensing images and the survey of geological records were identified sites that exemplify in a clear and objective manner the multiple environments and geological processes in which the rocks are formed. A comprehensive analysis of these outcrops allowed the characterisation of various types of metamorphic rocks and tectonic structures with high scientific, educational and ludic potentiality. The integration of the results gathered here with the new precepts of environmental conservation may make possible the implementation of a strategic management plan, so that the natural resources present in the park can be preserved and used in a wide manner by the community in general.